Demystifying interventional radiology : a guide for medical students - Athreya, Sriharsha (Springer, 2015)
This book is a concise introduction to the interventional radiology field and is designed to help medical students and residents understand the fundamental concepts related to image-guided interventional procedures and determine the appropriate use of imaging modalities in the treatment of various disorders. It covers the history of interventional radiology; radiation safety; equipment; medications; and techniques such as biopsy and drainage, vascular access, embolization, and tumor ablation. The book also describes the indications, patient preparation, post-procedure care, and complications for the most common interventional radiology procedures.